2019
DOI: 10.1038/s41598-019-51085-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced terahertz conductivity in ultra-thin gold film deposited onto (3-mercaptopropyl) trimethoxysilane (MPTMS)-coated Si substrates

Abstract: Various material properties change considerably when material is thinned down to nanometer thicknesses. Accordingly, researchers have been trying to obtain homogeneous thin films with nanometer thickness but depositing homogeneous few nanometers thick gold film is challenging as it tends to form islands rather than homogenous film. Recently, studies have revealed that treating the substrate with an organic buffer, (3-mercaptopropyl) trimethoxysilane (MPTMS) enables deposition of ultra-thin gold film having thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Au deposition is challenging due to its tendency to form islands instead of a continuous film. It is previously reported that the gold particles form disconnected island due to their surface diffusion in the early stages of the gold deposition by different fabrication methods [17]. The sizes of islands increase and then they coalesce to form a network by continued deposition.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Au deposition is challenging due to its tendency to form islands instead of a continuous film. It is previously reported that the gold particles form disconnected island due to their surface diffusion in the early stages of the gold deposition by different fabrication methods [17]. The sizes of islands increase and then they coalesce to form a network by continued deposition.…”
Section: Resultsmentioning
confidence: 98%
“…Regarding to the quality of a thin metal interlayer between dielectric components, the fabrication process generally gives rise to aggregated gold islands before a homogeneous layer is deposited [17]. Sytchkova et al [18] and Guske et al [19] both reported that the thickness of metal film should exceed 10 nm to prevent discontinuity of the interlayer coat.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the disk is modeled as gold with a conductivity of σ = 2 × 10 6 Sm ‐1 , which is over one order of magnitude lower than its bulk value, given its few‐nanometer thickness. [ 46 ] Because of the conductive layer, the electric field at the top surface of the cylinder is partially screened, leading to a significantly damped resonance at 0.61 THz, as shown in Figure 1f. In this case, the field of the first mode near 0.6 THz changes from an ellipse‐like shape to a cone‐like shape, and the zero electric field plane of the second mode near 0.61 THz shifts lower, as shown in Figure 1f.…”
Section: Resultsmentioning
confidence: 99%
“…For the THz transmission measurement, high-resistivity Si (∼1000 Ω cm) was used for the reference substrates, with the thin MWCNTs samples drop-cast onto them. Additionally, we calculated the complex refractive index in the frequency domain using the relationship between the THz transmission field and the refractive indices . According to the extracted indices, the complex conductivity of the thin MWCNT samples was described using the following equation: where ε ∞ represents the relative permittivity at a high frequency, ε 0 represents the permittivity of free space, and σ­(ω) represents the complex conductivity .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Additionally, we calculated the complex refractive index in the frequency domain using the relationship between the THz transmission field and the refractive indices. 56 According to the extracted indices, the complex conductivity of the thin MWCNT samples was described using the following equation:…”
Section: ■ Results and Discussionmentioning
confidence: 99%